Production of biodiesel from sludge palm oil by esterification using P-toluenesulfonic acid - Hayyan, Adeeb; Alam, Md. Zahangir; Mirghani, Mohamed Elwathig Saeed; Kabbashi, Nassereldeen Ahmed; Mohd Siran , Yosri; Mohd. Hakimi , Noor Irma Nazashida (2009)
Sludge palm oil (SPO) is an attractive feedstock and a significant raw material for biodiesel production. The use of SPO as feedstock for biodiesel production requires additional pretreatment step to transesterification process, which is an esterification process. The most commonly preferred catalysts used in this process are sulfuric, sulphonic, hydrochloric and P-toluenesulfonic acid (PTSA). In this study biodiesel fuel was produced from SPO using PTSA as acid catalyst in different dosages in presence of alcohol to convert free fatty acid (FFA) to fatty acid methyl ester (FAME). Batch esterification process of SPO was carried out to study the influence of PTSA dosage (0.25-10% wt/wt), molar ratio of methanol to SPO (6:1-20:1), temperature (40-80oC), reaction time (30-120 min). The effects of those parameters on FFA content, yield of treated SPO and conversion of FFA to FAME were monitored. The study showed that the FFA content of SPO reduced from 22% to less than 0.15% using ratio of 0.5, 0.75, 1, 1.5, and 2% wt/wt PTSA to SPO. After esterification process dosage of PTSA at 0.75% wt/wt shows the highest conversion of FFA to FAME as well as yield of treated SPO. The optimum condition for batch esterification process was 10:1 molar ratio, temperature 60oC and 60 minutes reaction time. The highest yield of biodiesel after aftertransesterification process was 76.62% with 0.06% FFA and 93% ester content.